Religious Schools, Social Values, and Economic Attitudes: Evidence from Bangladesh - Asadullah, Mohammad Niaz (2012)
This paper uses new data on female graduates of registered secondary secular schools and madrasas from rural Bangladesh and tests whether there exist attitudinal gaps by school type and what teacher-specific factors explain these gaps. Even after controlling for a rich set of individual, family, and school traits, we find that madrasa graduates differ on attitudes associated with issues such as working mothers, desired fertility, and higher education for girls, when compared to their secular schooled peers. On the other hand, madrasa education is associated with attitudes that are still conducive to democracy. We also find that exposure to female and younger teacher is associated with more favorable attitudes among graduates.